Catherine Michael Chin, Life: The Natural History of an Early Christian Universe - Wagenfuhr, Gregory (Journal for the study of religion, nature and culture, 2025)
Catherine Michael Chin, Life: The Natural History of an Early Christian Universe (Oakland: University of California Press, 2024), 258 pp., $ 29.95 (pbk), ISBN: 9780520400689.